Penyuluhan Hukum atas Disahkannya Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana bagi Peserta Penerima Manfaat Program Keluarga Harapan: Legal Counseling on the Enactment of Law Number 1 Year 2023 of the Criminal Code for Beneficiary Participants of the Program Keluarga Harapan - Adila, Arina Hukmu; Permonoputri, Rifi Maria Laila Fitri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Legal literacy among rural communities needs improvement. This community service initiative focuses on criminal law education, chosen because it is one of the branches of legal science closely related to the daily lives of the community. Especially in light of the enactment of Law No. 1 of 2023 on the Criminal Code, the community needs to understand the key differences between the new Criminal Code and the colonial-era Criminal Code. The types of criminal offenses discussed in this education program are also tailored to the legal needs of the community in Gedangan Village, Wirosari Subdistrict, Grobogan District. This community service initiative employs the Service Learning (SL) approach. SL is designed to integrate learning into community service activities. This method is implemented in the planning, implementation, and reflection stages. The activity was carried out smoothly and was enthusiastically received by the community. The presentation of the material also addressed legal issues occurring within the community benefiting from the Program Keluarga Harapan. The pre-test and post-test results showed an improvement from an average score of 3 to 7 (out of a total score of 10). This indicates an increase in the community's legal understanding before and after the legal education activity.